Brasileños asilados en México. Dos casos de excepción - Morales Muñoz, Daniela (El Colegio de México, A.C., 2020)
This article documents two peculiar cases of political asylum granted in exceptional circumstances by the government of Mexico to Brazilians who had been persecuted by the military regime. In the first case, between September 1969 and March 1970, the Gustavo Díaz Ordaz administration granted asylum to a score of political prisoners who had been released and immediately sent into exile, in accordance with the demands of a group of Brazilian revolutionaries who had kidnapped two employees of the embassies of the United States and Japan.The second case occurred in 1973, following the coup d’etat against the Salvador Allende administration in Chile. As part of the Mexican government’s solidarity with the people of Chile, it offered diplomatic asylum to a group of 43 Brazilians who were being persecuted by Chile’s military government, but once they arrived in Mexico, they were denied territorial asylum, forcing them to search for another asylum country.These are two sui generis asylum cases, as they occurred in situations without precedent in any other community of exiles, and so they are illustrative and revealing of the variations in the application of asylum policy in Mexico, particularly during the second half of the 20th Century.